HISTOGENESIS OF MESODERMAL COMPONENTS OF HUMAN FETAL THYMUS - BASHIR KHAN; SANOBAR SHAIKH (International Journal of Pharma and Bio Sciences, 2014)
The present study is conducted to observe the early cellular events and histological maturity of mesodermal component of thymus. After ethical approval from the institutional ethics committee 53 human fetuses were obtained from department of Obstetrics and Gynecology with permission of head of department and written informed consent from respective parents. The gestational age was determined by menstrual history and Crown Rump length (CRL). The specimen were dissected through parasternal incision and processed in paraffin. The sections were taken by rotary microtome. The slides were stained by Haematoxylin & eosin, Massons trichrome and Periodic acid-Schiff (PAS) stains. Differentiation of thymus started at 9th week and all significant structural changes such as lobulation, appearance of blood vessels and corticomedullary differentiation were occured within 17th week and thereafter thymus showed microscopic growth and maturity. The findings of the present study are comparable with the findings of standard text books and previous workers.